Dyslipidaemia In Patients With Type 2 Diabetes Mellitus. - Eid, M; Mafauzy, M; Faridah, AR (2003)
The aims of the study-were to define the prevalence of dyslipidaemia, its correlation with glycaemic control and contributory factors of dyslipidaemia in type 2 diabetic patients.